Understanding school truancy among students from broken-home families: A case study of an integrated psychoanalytic, SFBC, and CBT approach - Malikatul Muluk; Muhammad Rizki; Ahmad Khobir Avisina Gimnastiar (Eduvista: Journal of Education and Innovation, 2026)
Student truancy is commonly viewed as a disciplinary issue, although studies integrating multiple counseling approaches to address its underlying psychological causes remain limited. This study aimed to examine behavioral change in a truant student from a broken-home family through an integrated Psychoanalysis, Solution-Focused Brief Counseling (SFBC), and Cognitive Behavioral Therapy (CBT) approach. A qualitative case study design was employed using observation, semi-structured interviews, documentation, and the Beck Depression Inventory-II (BDI-II), with data analyzed through the Miles, Huberman, and Saldaña model. The findings revealed that truancy resulted from the interaction of family breakdown, economic hardship, limited transportation access, and low social support, which developed into emotional conflict and depression. The integrated intervention reduced the participant's BDI-II score from 25 to 9, accompanied by improved school attendance, emotional openness, and classroom engagement. This study contributes by proposing a conceptual model explaining behavioral change in truancy through the integration of Psychoanalysis, SFBC, and CBT. Abstrak Perilaku membolos pada peserta didik sering dipandang sebagai persoalan kedisiplinan, padahal penelitian mengenai integrasi berbagai pendekatan konseling untuk mengatasi akar psikologis perilaku tersebut masih terbatas. Penelitian ini bertujuan menganalisis perubahan perilaku membolos pada siswi yang mengalami broken home melalui pendekatan integratif Psikoanalisis, Solution-Focused Brief Counseling (SFBC), dan Cognitive Behavioral Therapy (CBT). Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus melalui observasi, wawancara semi-terstruktur, dokumentasi, dan Beck Depression Inventory-II (BDI-II) yang dianalisis menggunakan model Miles, Huberman, dan Saldaña. Hasil penelitian menunjukkan bahwa perilaku membolos dipengaruhi oleh broken home, tekanan ekonomi, keterbatasan transportasi, dan rendahnya dukungan sosial yang berkembang menjadi konflik emosional dan depresi. Intervensi integratif berhasil menurunkan skor BDI-II dari 25 menjadi 9, disertai meningkatnya kehadiran di sekolah, keterbukaan emosional, dan keterlibatan belajar. Penelitian ini berkontribusi dengan menawarkan model konseptual perubahan perilaku membolos melalui integrasi Psikoanalisis, SFBC, dan CBT.